Konserwacja i rekonstrukcja rękawicy skórzanej z Wyspy Spichrzów w Gdańsku - Nowak, Sebastian (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
The article presents brief characteristics of protective gloves, based on an example of an artifact excavated during archaeological exploration of a „Babel” granary at Żytnia street in Gdańsk. The object was treated and reconstructed in The Documentation and Conservation Laboratory of The Institute of Archaeology, NCU in Toruń. The article includes conservation issues, the program and description of treatments implemented working on the object, as well as the problem of importance of archaeological objects’ reconstruction to demonstrate technological processes and crafts of creating the items, especially to the public not being involved in scientific problems and having difficulties in perception of destroyed artifacts, deprived of their cultural contexts.